Simultaneous Boron and Nitrogen Doping in reduced graphene Oxide: Effects on optoelectronic performance - Yilmaz, Mehmet; Yaman, Mehmet; Erdogan, Erman; Yildirim, Fatma; Aydoan, Sakir (Elsevier, 2026)
Recently, photodetectors (PDs) made from reduced graphene oxide (rGO) have emerged as a promising candidate for optoelectronic applications. Here, we report the preparation of boron (B) and nitrogen (N) co-doped rGO structure and its applications for PDs. The results show that B and N co-doped rGO/n-Si device exhibit excellent PD properties under light intensities as well as UV and IR lights. The PD properties under UV-vis light intensities and different wavelengths of light were investigated as a function of the applied voltage. The photocurrent value of the fabricated device was maximized at a wavelength of 590 nm and exhibited photosensitivity. The maximum sensitivity (R) value was 54.28 mA/W for the 150 mW/cm2 light intensity, and 0.49 A/W for the 590 nm wavelength. In addition, detectivity (D*), Noise equivalent power (NEP), Ratio of Normalized Photocurrent to Dark Current (NPDR), and External quantum efficiency (EQE) values of the photodiodes were calculated. In accordance with previous studies, it was observed that the R and D* values decreased with increasing power density at zero bias voltage.
Keywords: Reduced graphene oxide; Heterojunction photodetector; Nitrogen/boron co-doping; Photodetection; Responsivity